Cell wall polysaccharides released during the alcoholic fermentation by Schizosaccharomyces pombe and S. japonicus: quantification and characterization. (February 2017) - Domizio, P.; Liu, Y.; Bisson, L.F.; Barile, D.
Abstract: The present work demonstrates that yeasts belonging to the Schizosaccharomyces genus release a high quantity of polysaccharides of cell wall origin starting from the onset of the alcoholic fermentation. By the end of the alcoholic fermentation, all of the Schizosaccharomyces yeast strains released a quantity of polysaccharides approximately 3–7 times higher than that released by a commercial Saccharomyces cerevisiae yeast strain under the same fermentative conditions of synthetic juice. A higher content of polysaccharide was found in media fermented by Schizosaccharomyces japonicus with respect to that of Schizosaccharomyces pombe . Some of the strains evaluated were also able to produce high levels of pyruvic acid, which has been shown to be an important compound for color stability of wine. The presence of strains with different malic acid consumption patterns along with high polysaccharide release would enable production of naturally modified wines with enhanced mouth feel and reduced acidity. The chemical analysis of the released polysaccharides demonstrated divergence between the two yeast species S. pombe and S. japonicus . A different mannose/galactose ratio and a different percentage of proteins was observed on the polysaccharides released by S. pombe as compared to S. japonicus . Analysis of the proteins released in the media revealed the presence of a glycoprotein with a molecular size around 32–33 kDa only for the species S. japonicus . Mass spectrometry analysis of carbohydrate moieties showed similar proportions among the N -glycan chains released in the media by both yeast species but differences between the two species were also observed. These observations suggest a possible role of rapid MALDI-TOF screening of N -glycans compositional fingerprint as a taxonomic tool for this genus. Polysaccharides release in the media, in particular galactomannoproteins in significant amounts, could make these yeasts particularly interesting also for the industrial production of exogenous polysaccharide preparations. Highlights: Schizosaccharomyces yeasts showed higher capacity to release polysaccharides as compared to S. cerevisiae . S. japonicus strains released higher quantity of polysaccharide with respect to S. pombe strains. Polysaccharides analysis showed divergence between S. pombe and S. japonicus . An intraspecific similarity of the glycans profile was observed. Rapid glycan fingerprint by MALDI TOF could be used as a taxonomic tool for these yeasts.